HTML5 graphics & data visualization cookbook - Fhala, Ben (Quick answers to common problems., 2012)
This cookbook is organized in a linear, progressive way allowing it to be read from start to finish, as well as to be used as a useful resource for specific tasks. The HTML5 examples and recipes will have you making dynamic, interactive, and animated charts and graphs in no time. You don't need to have a background in HTML5 or Canvas but you do need to have a basic understanding of how HTML works and know how to code in any language (preferably in JavaScript). In this book we will not explain how to learn to code but how to create projects and how to plan and execute them in the process.